Factors influencing late antenatal care of Muslim pregnant women: A predictive correlational study in Aceh, Indonesia - Fajarina, Mira; Terathongkum, Sangthong; Lininger, Jiraporn (Belitung Raya Publisher - Belitung Raya Foundation, 2024)
Background: Late antenatal care (ANC) has significant implications for maternal and infant morbidity and mortality among Muslim pregnant women in Indonesia. Existing literature has primarily focused on gestational weeks at the first ANC contact, with limited attention to the total number of ANC visits. Objective: This study aimed to explore the factors predicting late antenatal care contact among Muslim pregnant women, including the gestational weeks of the first ANC contact and the total number of ANC visits in Aceh, Indonesia. Methods: A predictive correlational study design was utilized. Eighty postpartum women who received late ANC were purposively sampled and included in the study. Data were collected in May 2023 using ANC knowledge, beliefs, and social support questionnaires. Statistical analyses included descriptive statistics, Spearman’s rank correlation, Chi-Square tests, and binary logistic regression with the enter method. Results: Pregnant women residing farther from home to ANC services were more likely to have their first ANC contact after 20 weeks than those with a shorter distance (AOR = 1.06; 95% CI: 1.02-1.10; p = 0.007). Additionally, women with a history of multiple abortions were more inclined to have four or more ANC visits compared to those with fewer abortions (AOR = 6.78; 95% CI: 1.64-28.09; p = 0.008). Conclusion: Distance from home to healthcare services emerged as a significant barrier to ANC contact, while a history of abortion appeared to motivate pregnant women to seek ANC more frequently. To address these issues effectively, nurses should consider implementing telemedicine services for ANC provision, integrating information on pregnancy complications to better support pregnant women in their care journey.